PELATIHAN MANAJEMEN KELAS BAGI GURU DI SMP IT MADANI KOTA PEKANBARU - Rahmat, Zetri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This community service program aims to enhance classroom management skills for teachers at SMP IT Madani Kota Pekanbaru. The training used Participatory Action Research (PAR) methodology, involving teachers actively in designing and implementing effective classroom management strategies. The program consisted of theoretical sessions on classroom management techniques, followed by interactive workshops and simulations to practice these techniques. Direct mentoring was also provided to help teachers address specific classroom challenges. The results showed that teachers gained more confidence and were ready to apply new strategies, creating a more conducive classroom environment that supports effective learning. This program not only improved classroom management skills but also contributed to the overall quality of education at the school.